Enhancement of beta rebound elicited by proprioceptive stimulation in the sensorimotor cortex by transcranial alternating current stimulation matched to the dominant beta frequency - Mayu Akaiwa; Ryo Kurokawa; Yuya Matsuda; Yasushi Sugawara; Rin Kosuge; Hidekazu Saito; Eriko Shibata; Takeshi Sasaki; Kazuhiro Sugawara (Neuroscience Research)
Transcranial alternating current stimulation (tACS) can modulate endogenous brain oscillations in a frequency-specific manner. Previous studies have reported that beta tACS modulates the excitability of primary motor cortex and improves task performance. Tactile and proprioceptive stimuli also elicit event-related synchronization of the beta rhythm in contralateral sensorimotor cortex, termed beta rebound, and a strong correlation was reported between proprioception-induced rebound strength and clinical recovery in stroke patients. We investigated the effects of tACS matched to the dominant beta frequency on the strength of proprioception-induced beta rebound.We recorded the beta rebound from 14 healthy young adults in response to passive index finger movement by electroencephalography to determine individual peak beta frequency. Electroencephalograms (EEG) were recorded during passive movements before and after active or sham tACS. We recorded beta rebound of all participants to determine their individual peak frequency of beta rebound prior to this experiment. Active tACS at individually matched frequencies increased beta rebound strength during subsequent passive movement compared to sham tACS in the majority of participants, while the remaining participants demonstrated no significant change or a decrease. These findings on healthy participants provide an essential foundation for further studies on the effects of beta frequency-matched tACS for stroke patient rehabilitation.